River Pollution in Riverside Stilt-House Communities: An Environmental Fiqh Perspective from Kahayan River, Indonesia - Ahmad Ridhoni (Mir'ah: Family Law and Legal Culture, 2026)
River pollution in riverside stilt-house communities has become a significant environmental issue that threatens ecosystem sustainability and public health. This study aims to analyze river pollution in the Kahayan River from the perspective of fiqh al-bi'ah (Islamic environmental jurisprudence) by examining the relevance of Islamic legal principles to environmental conservation. The research employed a normative legal approach based on library research using the Qur'an, Hadith, classical and contemporary fiqh literature, books, and scientific journal articles. Data were analyzed descriptively and analytically by relating the concepts of ḥifẓ al-bi'ah, fasād fi al-arḍ, maqāṣid al-sharī'ah, and the legal maxim adh-dhararu yuzāl to the phenomenon of river pollution. The findings reveal that river pollution is driven not only by inadequate sanitation infrastructure but also by long-standing socio-cultural practices and the limited internalization of environmental values in religious life. From the perspective of Islamic environmental jurisprudence, such practices constitute mafsadah and contradict the objectives of Islamic law aimed at protecting life, property, future generations, and the environment. Therefore, sustainable solutions require the integration of religious environmental education, adequate sanitation facilities, and community-based environmental regulations involving government, religious leaders, and local communities. This study contributes to the development of Islamic environmental jurisprudence by providing a contextual framework for integrating Islamic legal values into river conservation efforts. However, the study is limited by its normative approach and does not incorporate empirical evidence from community behavior, suggesting the need for future empirical and mixed-methods research.